Paciente de sexo masculino de 65 años de edad con insuficiencia renal crónica. - Guerrero Vera, Jessica Alexandra (2018)
Chronic renal failure is a catastrophic disease. Its main causes are hypertension and diabetes. Kidney damage occurs slowly over several years and many people do not suffer any symptoms until the disease is very advanced, and the main complication that occurs in a patient with chronic renal failure is anemia. When suffering from chronic renal failure it is important to reduce the protein intake since the proteins have a high molecular weight and can affect the kidney (the colander) more than it already is. It is important to have controlled the contribution of Potassium Phosphorus, Sodium. The general objective of my clinical case was to intervene with integral nutritional care to the patient with chronic renal failure. Comprehensive nutritional intervention was performed on a 65-year-old patient with chronic renal insufficiency in the anthropometric, clinical and dietary biochemistry, for interpretation of results. Follow-up was done for a period of 3 months where improvement was observed in the anthropometric, in the biochemical there was no improvement in the physical if and in the dietary there were changes in the diet.